Towards Understanding the Relation between Religions and Cultures in Southeast Asia (American Journal of Islam and Society, 2007)
In the face of modernity and its erosion of traditional values, weneed to preserve something of the wisdom of traditional culture.The traditional cultures have taken thousands of years to evolveand are necessary to preserve. They are the carriers of the accumulatedwisdom of the people since Antiquity. They give man asense of belonging, acceptance, and assurance. They enshrine thevalues, which define meaning, guide, motivate, and lead peopleto fulfillment. We find cultural traditions still alive in the ruralcommunities of Southeast Asia. It is to these communities thatwe need to turn to guide us on our road to the future ...